PRAKTIK SENDE SAWAH DALAM TINJAUAN HUKUM ISLAM (Studi Kasus Di Desa Sumbersari Kecamatan Srono Kabupaten Banyuwangi) - Abdul Kholiq Syafa'at; Nurul Inayah; Nawal Ika Susanti; Mohamad Al Kafi (Jurnal Istiqro, 2022)
This study aims to determine the practice of sende in Sumbersari Village, Srono District, Banyuwangi Regency and to find out the review of Islamic law on the practice of sending rice fields in Sumbersari Village, Srono District, Banyuwangi Regency. The type of research used by the author in completing this thesis is descriptive qualitative research. The analytical tool used in this research is an interactive model. The results obtained from research on the practice of sending in Sumbersari Village. The practice of the pawn contract (Sende) for the fields is as follows: First, Rahin goes to the murtahin to make an agreement on how much debt is requested and the field for which the contract is made marhun, after getting the agreement of the contracting party, the contract is rahn (Sende) accompanied by a witness. From the results of the study, it can be concluded that the practice of pawning (sende) rice fields that occurred in Sumbersari Village, Srono District, Banyuwangi Regency was in accordance with applicable Islamic law. Because it has fulfilled the terms and conditions of Islam. From the results of the research conducted, it can be concluded that the practice of pawning with the sende system in Sumbersari Village is legal, because it is in accordance with the requirements and pillars of rahn, namely: aqidain, ma'qud alaih, and shighat and avoids several possible facades, such as usury and gharar.